Comparative assessment of the efficacy of onabotulinumtoxinA and oral therapies (anticholinergics and mirabegron) for overactive bladder: a systematic review and network meta‐analysis. (2nd August 2017) - Drake, Marcus J.; Nitti, Victor W.; Ginsberg, David A.; Brucker, Benjamin M.; Hepp, Zsolt; McCool, Rachael; Glanville, Julie M.; Fleetwood, Kelly; James, Daniel; Chapple, Christopher R.
Abstract : Objectives: To compare the efficacy of onabotulinumtoxinA, mirabegron, and anticholinergics in adults with idiopathic overactive bladder (OAB) using network meta‐analysis (NMA). Patients and Methods: Information sources were searched for blinded randomised controlled trials (RCTs), of ≥2 weeks duration, comparing any dose of onabotulinumtoxinA, eligible oral/transdermal anticholinergics, or mirabegron, with each other or placebo, in adults with OAB. Bayesian random‐effects models were used to synthesise the results at week 12: NMA for responder analyses and network meta‐regression (NMR) for change from baseline analyses. The NMR was used to adjust for differences in baseline severity between studies. Sensitivity analysis, excluding studies considered to be at a high risk of methodological bias, was conducted. Results: In all, 56 RCTs were included in the networks. For each outcome, results are reported for all licensed treatment doses. For each NMR, results are based on patients with an average number of episodes of the outcome at baseline. After 12 weeks, all treatments were more efficacious than placebo. Patients who received onabotulinumtoxinA (100 U) had, on average, the greatest reductions in urinary incontinence episodes (UIE), urgency episodes, and micturition frequency, and the highest odds of achieving decreases of 100% and ≥50% from baseline in UIE/day. When comparing onabotulinumtoxinA with other pharmacotherapies, mean differences favoured onabotulinumtoxinA 100 U over all comparators for UIE and urgency episodes (credible intervals excluded zero) and all but two of the comparators for micturition frequency. OnabotulinumtoxinA 100 U was also associated with higher odds of achieving a 100% and ≥50% decrease in UIE/day than most other licensed treatments in the network. The exclusion of studies with a high risk of bias had little impact on the conclusions. Conclusion: The results indicate that, after 12 weeks, onabotulinumtoxinA 100 U provides greater relief of OAB symptoms compared with most other licensed doses of other pharmacotherapies in the network.